Homo- and Heterotypic Trajectories in a Preschool to Primary-School Clinical Sample: A Prospective Study Related to Maternal Psychopathology - Jobs, Isabell; Müller, Jörg Michael; Skorozhenina, Olena; Romer, Georg (Frontiers in Psychiatry, 2019)
Background: Most longitudinal or follow-up mental health studies describe developmental pathways using dimensional measures of psychopathology, but seldom using pathways described by clinical disorders. Objective: We aim to describe diagnostic pathways by homotypic (within the disorder continuity) and heterotypic development (between the disorder continuity), with maternal psychopathology as moderator for both trajectories. Methods: Clinically referred children (0–7 years; N = 83) were assessed at preschool age and at primary-school age through a clinical interview. We built a disorder cluster of emotional disorders (ED; F32, F40, F42, F43, F93.0, F93.1, F93.2, F93.8, F95), behavioral disorders (BD; F68.8, F90, F91, F91.3, F93.3, F93.9, F94), and specific early onset disorders (SEO; F50, F51, F70, F98.0, F98.1, F98.2, F98.8, F98.9). We describe the prevalence, comorbidity, and clinical trajectories of various types of homotypic and heterotypic development. Results: We observed a high rate of comorbidity throughout the study (62.6% at admission and 67.5% at follow-up) and in general, a high continuity of mental health problems from preschool to primary-school age children (69.9% of the sample showed continuity), with 50.6% of the sample showing homotypic and 44.6% showing heterotypic development. Hierarchical multiple regression analyses suggest that heterotypic development may be influenced by maternal psychopathology. Conclusion: Currently, evidence-based mental health guidelines for preschool populations are designed and evaluated assuming a homotypic development. However, our findings indicate that treatment interventions and outcome measures should also be designed and evaluated for heterotypic development especially in case of increased maternal psychopathology.